Fisheries at Rambungan mangrove area - Sabriya, bt. Abdull Jabbar (Faculty of Resource Science and Technology, 2008)
Thi, study wa, carried out to determine the present status of fisheries at Rambungan Mangrove Area. Field samplings were carried out for three times in October and December 2007 and March 2008 at five selected stations in the study area. A total of 120 individuals comprising IS families and 20 species were caught from the five study stations. Four main villages were found in Rambungan mangrove area. Fishing methods employed by the villagers were mainly driti net, gill net and small trawlers. The main commercial species found at Rambungan mangrove area were Arius spp., Epinepho/us spp., Leiognafhus spp., Penaeus spp. and Scylla spp. From the survey and interviews carried out it showed that Rambullgan mangrove area is an important fish ing ground for the vi lIagers.